Exploring the role of large language models during the culture shock phase: A study of international students in Japan - Hsieh, ChunPi; Ochiai, Yoichi; Matsuda, Ichiro; Fushimi, Tatsuki; Li, Jingjing (Journal of International Students, 2026)
International students face cultural challenges during culture shock, leading to distress and social isolation. University support lacks personalization, leaving students to rely on informal tools such as translation apps and social media that perform poorly in complex situations. Large Language Models offer multilingual support, yet their role in international students’ cultural adaptation remains underexplored. This study examines how LLMs support culture-related everyday tasks in Japan, where implicit institutional norms intensify difficulties. We conducted a two-phase study: a pre-survey (N = 103) identified barriers and informed four scenarios (hair appointments, clinic visits, bank account opening, and garbage classification), followed by a user study (N = 40) comparing GPT-4o, Claude, Gemini, and Google Translate. Results show that breakdowns stemmed less from vocabulary than from uncertainty about institutional expectations and appropriate action. Participants used LLMs not only for translation but also for reassurance and sensemaking.